Wood surface finishing of selected invasive tree species : Površinska obrada nekih invazivnih vrsta drva - Pavlič, Matjaž (Array, 2020)
Due to their strong renewal power, the invasive tree species are spreading rapidly, especially in abandoned agricultural and forest areas and along traffic routes and water courses. One way of their restriction is the promotion of their use. In our research, we investigated surface finishing of wood of five selected invasive species in Slovenia, Box elder (Acer negundo L.), Black locust (Robinia pseudoacacia L.), Horse-chestnut (Aesculus hippocastanum L.), Honey locust (Gleditsia triacanthos L.) and Chinese sumac (Ailanthus altissima (Mill.) Swingle), and compared it with the finishing of the European beech (Fagus sylvatica L.) wood. For coatings, we selected one-component waterborne finish on acrylate-polyurethane basis, one-component solventborne finish on polyurethane basis and tung oil as a natural finish. Several surface properties were investigated. We proved that surface hardness, resistance to impact and adhesion were very much related to interactions between the coating and the substrate, while resistance to cold liquids was only dependant on the type of the finish. It was also shown that, in general, finishing of woods of selected invasive tree species was not problematic. The only exception was Black locust wood on which tung oil cured very slowly.